Tuhan dalam Perspektif Islam Kejawen:: Refleksi Teologis di Perbatasan Enkulturasi dan Sinkretisme - Hakim, Lukman; Aziz, Achmad As'ad Abd. (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
Plurality is a sunnatullah that cannot be avoided. Plurality is very possible because the natural world and everything in it is dynamic and tentative. In every change that involves humans, it is impossible to imagine a single change taking place, including regarding the notion of religious belief and divinity (theology). This research is included in the qualitative research of the library (Library Research), in which researchers will try to examine the literature about God in the Perspective of Kejawen Islam. This study uses an interpretive approach. Javanese culture or Kejawen that is adaptive are very likely to accommodate changes that are enculturative or syncretic. Islam, like Javanese culture, is also quite adaptive and accepts every adjustment. However, it is very clear that Islam does not accept adaptation in any form in the realm of aqeedah. This research is intended to determine the boundaries between enculturation and syncretism, through qualitative methods based on literature studies and descriptive analysis. The results obtained are that Kejawen is generally enculturative in nature, but there are also several kejawen schools that apply syncretism.